Phage biocontrol success of bacterial wilt depends on synergistic interactions with resident rhizosphere microbiota - Sara Franco Ortega; Bryden Fields; Daniel Narino Rojas; Lauri Mikonranta; Matthew Holmes; Andrea L. Harper; Ville‐Petri Friman (Microbial Biotechnology)
Abstract Phages can successfully be used in vitro and in planta to biocontrol the phytopathogenic Ralstonia solanacearum bacterium—the causal agent of bacterial wilt disease. However, phage biocontrol outcomes are still variable, and it is unclear what causes this. In this study, we assessed the efficiency of four phages in controlled in vitro and in planta experiments in all one‐ and two‐phage combinations. We found that using phages in combination did not improve the phage biocontrol efficiency relative to single phage treatments, while certain phages and their combinations were more effective than the others. High intra‐treatment variability in phage efficiency was observed across all phage treatments, which was associated with clear shifts in microbiome composition, a reduction in R. solanacearum and an increase in phage densities. We further identified the bacterial taxa that were associated with these ‘shifted’ microbiomes and conducted additional plant growth experiments, demonstrating that some of the enriched bacterial species could protect plants from R. solanacearum infections—a pattern which was also observed using partial least squares path modelling (PLS‐PM). Together, these results suggest that phages could open niche space for beneficial bacteria by reducing pathogen densities and that variability in phage biocontrol outcomes is rhizosphere microbiome‐dependent, which can introduce between‐replicate variation, even in controlled greenhouse conditions.